Effect of various phosphate fertilizers on growth and antioxidant activity of Euglena gracilis Klebs, 1883 IDN22 isolated from Dieng Peatland, Indonesia - Eko Agus Suyono; Budiman, Arief; Dewayanto, Nugroho; Kurniawan, Indira Amani; Marwadani, Laila Mei; Renisha Windy Puspita Sari; Setyaningrum, Sri; Renata Adaranyssa Egistha Putri (Agriculture and Natural Resources, 2026)
Importance of the work: A cost-efficient, phosphate fertilizer-based medium could improve the economic feasibility of Euglena gracilis Klebs, 1883 production for food industry applications. Objectives: To assess the effect of different phosphate fertilizer types on the growth and antioxidant activity of the indigenous isolate E. gracilis IDN22. Materials and Methods: Batch cultivation (150 L) of the local isolate E. gracilis IDN22 was conducted in separate tanks for each treatment, using media supplemented with various phosphate fertilizers: triple super phosphate (TSP), diammonium phosphate (DAP), monoammonium phosphate (MAP) and fused magnesium phosphate (FMP). Technical replicates (n = 3) were collected for the analysis. The observed variables were: cell growth (measured using a Neubauer counting chamber); biomass production (using the filtration method); pigment concentration and productivity (analyzed using spectrophotometry); and antioxidant activity (assessed using the 2,2 diphenyl-1-picrylhydrazyl method based on half maximal inhibitory concentration (IC50) values). Results: The DAP treatment produced the highest cell density in the exponential phase on day 13, while the MKP treatment had the highest growth rate (µmax = 0.736). In contrast, the FMP treatment had the highest values for biomass content, pigment productivity and absolute pigment. In addition, the MKP treatment had the highest antioxidant activity (IC50 = 4.172 mg/mL), while FMP had the lowest antioxidant activity (IC50 = 12.647 mg/mL). Main finding: The findings offer a scientific basis for selecting fertilizers that support sustainable and efficient microalgae production for food industry applications.